Democracy Needs Rebellion: A Democratic Theory Inspired by Albert Camus. Issue 161 (1st December 2019) - Pausch, Markus
Abstract : Democracy has come under pressure in many countries in recent years. Authoritarian tendencies, populism and the cult of leadership threaten pluralistic societies in Europe and other parts of the world. But democracy is more than just a method of finding a majority; it is inextricably linked to the fight against oppression and injustice in all contexts of life. Especially in times of democratic crisis, it is necessary to focus on its core aspects. The political thinking of French philosopher and writer Albert Camus, who died in 1960, offers the basis for a redefinition of democracy that is linked to and dependent on rebellion. From his reflections, a radical theory of democracy can be derived that is based on the absurdity of the world, its incompleteness, revolt and resistance to authoritarianism, on doubt, dialogue and foreignness.